基于Matlab的异形片刹车机构的多目标优化设计 - 李晓舟; 龙志伟; 邢向飞 (Jixie chuandong)
A structure scheme of the shaped piece brake is proposed for a certain kind of inspection robot working on ultra high voltage transmission line.The mathematical model and mechanical model are established based on geometric parameters of the component.With the numerical analysis software Matlab,the multi-objectively plan and optimization design of shaped piece brake mechanism are realized.By means of the finite element analysis software ANSYS,the mechanism model is analyzed about strength and deformation before and after its optimization design,the results verify the mechanical model is reasonable and the optimization design is feasible.